Mobile Application Design for Student Learning - Angelina; Weliati; Edwin Christian Jonatan Wardoyo; Sugiarto Hartono (Advances in Science, Technology and Engineering Systems Journal, 2021)
The research objectives were to identify, analyze needs, as well as designing a mobile application for student online learning at PT. Ruang Raya Indonesia, particularly in the process of working on tasks assigned by the teacher. The methods used in this research are data collection method using Slovin theory, systems analysis by focusing on the current business processes, designing object-oriented systems (OOAD) method. The result is the design of mobile applications in the form of an application for students to be able to do the tasks assigned by the teacher, change private tutoring schedule, and view academic progress reports of the student during private tutoring. The Conclusion of this research is PT. Ruang Raya Indonesia requires a system that can provide students the information about student’s private tutoring activity.
Keywords: Mobile Application; Online Learning; Assignment; Report; OOAD